2013
DOI: 10.1016/j.compmedimag.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optimized b-value sampling schemas for diffusion kurtosis imaging with an application to stroke patient data

Abstract: Diffusion kurtosis imaging (DKI) is a new method of magnetic resonance imaging (MRI) that provides non-Gaussian information that is not available in conventional diffusion tensor imaging (DTI). DKI requires data acquisition at multiple b-values for parameter estimation; this process is usually time-consuming. Therefore, fewer b-values are preferable to expedite acquisition. In this study, we carefully evaluated various acquisition schemas using different numbers and combinations of b-values. Acquisition schema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In this study, the accuracy was substantially higher of DKI maps obtained from the dataset with the bvalue combination of 0, 1000, and 2500 s/mm 2 than with the combination of 0, 1000, and 2000 s/mm 2 , indicating that uneven intervals will satisfy the requirement for both high accuracy and short acquisition time. Our findings agreed with the previous study 20 that demonstrated that b-values at uneven intervals are optimal for the accuracy of the MK map. Our results further confirmed that those bvalues are also optimal for the accuracy of K ¬ and K ¦ maps.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, the accuracy was substantially higher of DKI maps obtained from the dataset with the bvalue combination of 0, 1000, and 2500 s/mm 2 than with the combination of 0, 1000, and 2000 s/mm 2 , indicating that uneven intervals will satisfy the requirement for both high accuracy and short acquisition time. Our findings agreed with the previous study 20 that demonstrated that b-values at uneven intervals are optimal for the accuracy of the MK map. Our results further confirmed that those bvalues are also optimal for the accuracy of K ¬ and K ¦ maps.…”
Section: Discussionsupporting
confidence: 83%
“…For comparison between DWI, DTI, and DKI, see Table 1. Several recent studies demonstrate that DKI in general has even higher accuracy as compared to DTI in various diseases including brain neoplasm [20,21], stroke [3,22,23], or neurodegenerative disorders [24][25][26][27][28]. This added diagnostic accuracy however has the price of longer acquisition times, which may among other problems increase head motion artifacts in patients.…”
Section: Diffusion Imagingmentioning
confidence: 94%
“…DKI metrics were computed using the Diffusion Kurtosis Imaging software (https://github.com/NYU-DiffusionMRI/Diffusion-Kurtosis-Imaging), and the following metrics were used in the group comparison: mean kurtosis (MK), fractional anisotropy (FA) and mean diffusivity (MD). We should note that metrics common to DTI and DKI (e.g., FA and MD) are not quantitatively the same if computed using one model or the other (Lanzafame et al, ; Yan et al, ).…”
Section: Methodsmentioning
confidence: 98%